Qualidade do ensino: uma nova dimensão da luta pelo direito à educação - Romualdo Portela de Oliveira; Gilda Cardoso de Araujo (Associacao Nacional de Pós-Graduação e Pesquisa em Educação, 2005)
The objective of this text is to analyse the Right to Education confronting the expansion of the access to elementary schooling during the last decades and the challenges of transforming the standard of quality for all into part of the public and subjective right to education. It is structured in three parts. In the first section, data pertaining to the evolution of access to schooling is analysed in connection with notions of teaching quality. In the second part, the dimension of the problem of quality is evidenced by means of an analysis of the Programme for International Student Assessment (PISA) results and their repercussions in Brazil. Finally, the possibilities of establishing a standard of quality as a necessary and urgent measure to guarantee the right to education are discussed. The conclusion highlights the theoretical and technical challenges to be faced in formulating a standard of quality that is, at one and the same time, comprehended by the population and can be made subject to legal demands.